ANALISIS PENDAPATAN DAN KELAYAKAN USAHATANI KACANG TANAH DI DESA POMBEWE KECAMATAN SIGI BIROMARU KABUPATEN SIGI - jauhar, andi (AgriSains, 2013)
Production of peanuts obtained does not guarantee high revenue to be received by the farmer. Although peanut production in the village of Pombewe was relatively high, this does not mean that the income is also high. Therefore, a study on the level of farm income and its feasibility are needed. This study aims to determine the level of income and the feasibility of peanut farming, conducted from May to Maret 2012. Location of study was selected on purpose by the consideration that the village of Pombewe is one peanut production areas in the sub district of Sigi Biromaru, Sigi Regency. The entire population of peanut farmers were used as respondents in the Pombewe village, Sigi District A total of 27 respondents were used in a single growing season, The primary data were colected by direct interview to respondents using a questionnaire and secondary data obtained from relevant institutions. The anaiysis used in this study is an analysis of the income and feasibility. The results showed that the overage farm income at village of Pombewe was Rp 4.615.907,41 per farm land (0,54ha/mt) with a value of r/c = 3,12 which means peanut farming in this region was feasible. Key words : income analysis, peanut farm, sigi district